Bangladesh : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report, 2005)
This Report on the Observance of Standards and Codes (ROSC) data module provides an assessment of Bangladesh's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. With some exceptions, the coverage, periodicity, and timeliness of macroeconomic statistics meet the GDDS recommendations. Guided by GDDS plans for improvement, the Bangladesh Bureau of Statistics, the Ministry of Finance, and the Bangladesh Bank have demonstrated commitment to continuously improve the compilation and dissemination of macroeconomic statistics.